CLRM-03 INCIDENCE OF INTRACRANIAL HEMORRHAGE IN GLIOMA PATIENTS WITH VENOUS THROMBOEMBOLISM CONVERTED FROM LMWH TO APIXABAN. (5th August 2022) - Aboud, Orwa; Ye, Xiaobu; Grossman, Stuart
Abstract: Venous Thromboembolism (VTE) occurs in approximately 15-30% of patients with glioma 1, 2 who are treated with therapeutic anticoagulants. Anticoagulation treatment increases the incidence of intracranial hemorrhage (ICH) with variable incidence between studies 1.9% to 20s% 3-6. The "common practice" treatment for VTE in glioma patients includes subcutaneous administration of low molecular weight heparin (LMWH, enoxaparin) injection, which requires daily self-injection. Switching glioma patients with VTE from LMWH to oral anticoagulants would limit the difficulty and the inconvenience of daily self-injecting in primary brain tumor patients and decrease the room for error in administering the dose along and the risk for heparin induced thrombocytopenia7. The goal of this project is to evaluate the incidence of intracranial hemorrhage in glioma patients with VTE converted from LMWH to Apixaban. We hypothesize that patients with brain tumors and Venous Thromboembolism can be converted safely from LMWH to Apixaban. To examine this hypothesis, we will enroll adult patients with pathologically confirmed supra-tentorial glioma and VTE, patient must have been treated with LMWH for ≥ 5 days. We will exclude patients with bleeding diathesis, severe hypersensitivity to Apixaban or pregnant or unable to provide informed consent. To assess the validity of our hypothesis: Primary Objective: To estimate the incidence of ICH in glioma patients with history of VTE after the conversion from LMWH to oral Apixaban. Secondary Objective: To estimate the incidence of recurrent VTE in glioma patients with history of VTE after the conversion from LMWH to oral Apixaban. To our knowledge, this is the first of its kind study to estimate the risk of ICH in glioma patients with VTE treated with oral anti-coagulation. Successful completion of our trial will provide answers to an important clinical question that could allow our patients using more convenient yet effective treatment by establishing and implementation of best practices.